Arguments for cycling as a mechanism for sustainable modal shifts in Bogotá. (February 2022) - Oviedo, Daniel; Sabogal-Cardona, Orlando
Abstract: As a clean, accessible and healthy transport alternative, the benefits of cycling have been well-documented and suggest positive health, environmental and affordability outcomes. Despite a favourable rhetoric for cycling, in many cities in Latin America, its uptake has gained more traction among younger and carless populations than frequent users of private motorised vehicles. Recognising this reality, our article poses arguments for cycling beyond its classic benefits via direct comparisons of its performance against that of private cars. Our paper compares cycling and car-based trips, presenting evidence in cycling for policy and decision-making targeting a demand segment that has historically been more resistant to modal shifts to sustainable mobility. We contrast performance of both modes in relation to coverage and accessibility, testing different modal shift scenarios in the context of Bogotá, Colombia's capital city. As a city that has been recognised in the international literature for both its successes in urban transport policy and its persisting mobility and access inequalities, Bogotá's contrasts are an ideal setting for this research. We build on a geo-coded household travel survey for 2015 and API-sourced datasets to develop spatial coverage and potential accessibility metrics for cycling and car-based trips. Findings suggest Bogotá's large potential for further increases in cycling, particularly from car-users, which can lead to overall societal gains in terms of sustainable accessibility and present a fertile ground for bike-sharing systems. The paper builds on spatially and socially distributed findings to identify areas with the highest potential for bike-sharing in Bogotá.